Three leg Chickens and White Horses that are no Horses: Theories and Paradoxes of Anciet Chinese Nomenalists - S. Rošker, Jana (Anali PAZU HD, 2022)
The present article introduces one of the most interesting philosophic school of ancient China, namely the School of names or the Nomenalist school. In many aspects, their discussions can be compared to the foundations of Western formal logic. However, they follow different approaches: the nomenalist philosophers were namely not primarily interested in the laws of cognition, but rather in its concrete applicability, i.e. in the art of “proper” reasoning as a precondition of precise expressions. The representatives of this school have thus laid stress upon modes of expression and semantic connotations of notions, on categorizations, the structuring and definitions that are written in the form of disputes. Thrugh the analyses of the works written by the three most significant representatives of this philosophic current, the author aims to surpass the prejudices that are still prevailing in Western philosophy and according to which ancient Chinese philosophy was exclusively based upon moral and proto-theological discourses.
Keywords: Chinese nomenalists; Ming jia; the School of names; classical Chinese logic; Chinese philosophy